(NmETODI^ESKIE UKAZANIQ K U^EBNIKAM PENIQ (BI-IV (NKLASSOW(B.s - (Na(B.(NbANDINAs; (Nm(B.(NrUMER(B.s (NDRUGOJ AWTORs ((NmOSKWAs (NmUZYKAs, 1968)
(NwOSPITANIE WSESTORONNE RAZWITOJ LI^NOSTI(B-(NOSNOWNAQ ZADA^A SOWETSKOJ [KOLY(B. s
Keywords: (NmETODIKAs